Pengaruh Gaya Kepemimpinan dan Disiplin Kerja terhadap Kinerja Personel Polres Pamekasan: Peran Produktivitas Kerja sebagai Variabel Mediasi - Latiefatul Fitrih N; Subijanto Subijanto; Chamariyah Chamariyah (Fakultas Ekonomi Universitas 45 Surabaya, 2025)
This study focuses on the influence of leadership style and work discipline on the performance of Pamekasan Police personnel, with work productivity functioning as a mediator that strengthens the relationship between these variables. Using a quantitative approach and involving 88 respondents, the analysis was conducted using the Structural Equation Modeling-Partial Least Squares (SEM-PLS) method. The findings of the study indicate that although leadership style has an insignificant negative effect on personnel performance, work discipline directly and significantly affects performance. Furthermore, work productivity plays a strategic role as a link that optimizes the influence of leadership style and work discipline on overall performance. Leadership style and work discipline also have a significant effect on work productivity, which in turn improves personnel performance. With a very high average for each variable: leadership style (4.15), work discipline (4.23), work productivity (4.25), and personnel performance (4.19) this study provides a clear picture of the importance of managing leadership style and improving work discipline in increasing productivity. These results offer strategic insights for Pamekasan Police to maximize personnel performance through effective leadership management and improving work discipline.